Answer:
the average rate of change is 4
Step-by-step explanation:
(f + g)(x) = f (x) + g(x)
= [3x + 2] + [4 – 5x]
= 3x + 2 + 4 – 5x
= 3x – 5x + 2 + 4
= –2x + 6
Answer:
The word "of" refers to multiplication.
Step-by-step explanation:
Multiplication is what to do in all word problems when we see the word "of"
Answer:
![\mathrm{The\:solutions\:to\:the\:system\:of\:equations\:are:x=-2,\:y=2}](https://tex.z-dn.net/?f=%5Cmathrm%7BThe%5C%3Asolutions%5C%3Ato%5C%3Athe%5C%3Asystem%5C%3Aof%5C%3Aequations%5C%3Aare%3Ax%3D-2%2C%5C%3Ay%3D2%7D)
Step-by-step explanation:
![\begin{bmatrix}-7x-6y=2\\ 7x+4y=-6\end{bmatrix}](https://tex.z-dn.net/?f=%5Cbegin%7Bbmatrix%7D-7x-6y%3D2%5C%5C%207x%2B4y%3D-6%5Cend%7Bbmatrix%7D)
![\mathrm{Substitute\:}x=-\frac{2+6y}{7}](https://tex.z-dn.net/?f=%5Cmathrm%7BSubstitute%5C%3A%7Dx%3D-%5Cfrac%7B2%2B6y%7D%7B7%7D)
![\begin{bmatrix}7\left(-\frac{2+6y}{7}\right)+4y=-6\end{bmatrix}](https://tex.z-dn.net/?f=%5Cbegin%7Bbmatrix%7D7%5Cleft%28-%5Cfrac%7B2%2B6y%7D%7B7%7D%5Cright%29%2B4y%3D-6%5Cend%7Bbmatrix%7D)
![\begin{bmatrix}-2-2y=-6\end{bmatrix}](https://tex.z-dn.net/?f=%5Cbegin%7Bbmatrix%7D-2-2y%3D-6%5Cend%7Bbmatrix%7D)
![\mathrm{For\:}x=-\frac{2+6y}{7}](https://tex.z-dn.net/?f=%5Cmathrm%7BFor%5C%3A%7Dx%3D-%5Cfrac%7B2%2B6y%7D%7B7%7D)
![\mathrm{Substitute\:}y=2](https://tex.z-dn.net/?f=%5Cmathrm%7BSubstitute%5C%3A%7Dy%3D2)
![x=-\frac{2+6\cdot \:2}{7}\\\\x=-2](https://tex.z-dn.net/?f=x%3D-%5Cfrac%7B2%2B6%5Ccdot%20%5C%3A2%7D%7B7%7D%5C%5C%5C%5Cx%3D-2)